Tuning the scale of α precipitates in β-titanium alloys for achieving high strength. (September 2018) - Mantri, S.A.; Choudhuri, D.; Alam, T.; Viswanathan, G.B.; Sosa, J.M.; Fraser, H.L.; Banerjee, R.
Abstract: The strength of a commercial β‑titanium alloy was tuned by systematically controlling the size-scale of α precipitation via two-step heat treatments. While the first step annealing at 350 °C forms the precursor metastable ω phase, the subsequent annealing at 600 °C/1H resulted in fine-scale α precipitation. We find that annealing duration at 350 °C greatly impacts the α size-scale and, this consequently can be used to tune the ultimate tensile strength (UTS) from 1 to 2 GPa. A combination of high volume-fraction of non-shearable super-refined α precipitates, coupled with their pyramidal arrangement, and a constrained β matrix leads to very high strength. Graphical abstract: Unlabelled Image